The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1210/endo.142.10.8421
|View full text |Cite
|
Sign up to set email alerts
|

Factors Derived from Adrenals Are Required for Activation of Cardiac Gene Expression in Angiotensin II-Induced Hypertension

Abstract: The mechanisms mediating the activation of cardiac gene expression during pressure overload are not fully understood. We examined whether angiotensin II-induced activation of ventricular gene expression is related to blood pressure and ventricular mass or requires other factors by infusing angiotensin II in sham-operated and adrenalectomized rats. In sham-operated rats, angiotensin II (33 microg/kg x h, sc) produced a significant increase in mean arterial pressure (measured by telemetry) within 3 h. Mean arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In agreement with previous studies, 12-15 PD123319 infusion alone had no effect on MAP; moreover, it did not modify Ang II-induced increase in blood pressure ( Figure 1A), showing that AT 2 -R is not involved in the regulation of blood pressure. As described previously, the increase in MAP by Ang II was associated with a significant decrease in heart rate, 16 remaining unaffected by PD123319 ( Figure 1B). Echocardiographic measurements showed that LV ejection fraction ( Figure 1C) and LV fractional shortening ( Figure 1D) were similar in all groups, suggesting that LV function was preserved in Ang II-induced hypertension.…”
Section: Hemodynamic Parameterssupporting
confidence: 85%
See 4 more Smart Citations
“…In agreement with previous studies, 12-15 PD123319 infusion alone had no effect on MAP; moreover, it did not modify Ang II-induced increase in blood pressure ( Figure 1A), showing that AT 2 -R is not involved in the regulation of blood pressure. As described previously, the increase in MAP by Ang II was associated with a significant decrease in heart rate, 16 remaining unaffected by PD123319 ( Figure 1B). Echocardiographic measurements showed that LV ejection fraction ( Figure 1C) and LV fractional shortening ( Figure 1D) were similar in all groups, suggesting that LV function was preserved in Ang II-induced hypertension.…”
Section: Hemodynamic Parameterssupporting
confidence: 85%
“…16 Full-length rat atrial natriuretic peptide (ANP) cDNA probe (a gift from Dr Peter Davies, Queen's University, Kingston, Canada), a 390-bp rat B-type natriuretic peptide (BNP) cDNA probe, and an 18S cDNA probe were prepared as previously reported. 16 cDNA probes for rat ␣-actin and myosin isoforms were made by reverse transcription-polymerase chain reaction (RT-PCR) and ligated to dT-tailed pCR2.1 vector by use of a TA Cloning Kit (Invitrogen).…”
Section: Isolation Of Cytoplasmic Rna and Northern Blot Analysismentioning
confidence: 99%
See 3 more Smart Citations